1998
DOI: 10.2307/3433823
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Functions in Industrial Workers after Exposure to 2,3,7,8-Tetrachlorodibenzo-p-dioxin: Dissociation of Antigen-Specific T-Cell Responses in Cultures of Diluted Whole Blood and of Isolated Peripheral Blood Mononuclear Cells

Abstract: A comparative analysis was performed of the phenotype and function of peripheral blood leukocytes of two age-matched cohorts of industrial workers in chemical plants, one of which was exposed occupationally to high concentrations of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Median actual TCDD burdens were 1 16 ng/kg and 4 ng/kg, respectively. The phenotype analysis of peripheral blood mononuclear cells (PBMC) revealed no significant differences in the proportions of CD3, CD4, or CD8+ T lymphocytes, of CD16+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…In contrast, Webb et al 3 reported a significant increase in CD8 percentages and a significant decrease in CD4/CD8 ratio in exposed subjects among residents of an environmentally contaminated site in Missouri, including dioxin contamination, as compared to non-exposed subjects. Another study among industrial workers showed a significant increase in CD8 counts among TCDD-exposed workers compared to the control group of non-exposed workers, although the CD4/CD8 ratio did not change significantly 10. However, other studies have found no difference in CD4 and CD8 counts and CD4/CD8 ratio among dioxin-exposed subjects as compared to non-exposed subjects 4 5 8 26–33.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, Webb et al 3 reported a significant increase in CD8 percentages and a significant decrease in CD4/CD8 ratio in exposed subjects among residents of an environmentally contaminated site in Missouri, including dioxin contamination, as compared to non-exposed subjects. Another study among industrial workers showed a significant increase in CD8 counts among TCDD-exposed workers compared to the control group of non-exposed workers, although the CD4/CD8 ratio did not change significantly 10. However, other studies have found no difference in CD4 and CD8 counts and CD4/CD8 ratio among dioxin-exposed subjects as compared to non-exposed subjects 4 5 8 26–33.…”
Section: Discussionmentioning
confidence: 94%
“…CD8 + (T cytotoxic) cells are essential for the control of the intracellular amostigate stages, these cells kill target cells presenting antigens in the appropriate context. 26 Ernst et al 29 claimed that the percentage of CD8 + cells was not affected in industrial workers after exposure to TCDD. Similarly, Huang and Koller 8 demonstrated that no significant change occurred in the CD8 + cell subpopulations after exposure to TCDD in rats.…”
Section: Discussionmentioning
confidence: 99%
“…33 CD161 + cells populations were decreased with TCDD exposure in rats. However, Ernst et al 29 claimed that NK cells were not significantly affected in industrial workers exposed to high concentration of TCDD in chemical plants. This disagreement between our study and that of Ernst et al 29 may be due to the longer exposure time in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study conducted on workers exposed to high concentrations of TCDD in chemical plants, no significant differences were detected in the proportion of CD 4+ , CD 8+ lymphocytes, CD 16+ natural killer cells, and CD 19 B lymphocytes among the exposed workers compared to the controls. (38) . These controversy in the results may be attributed to exposure to different toxic compounds and different levels of exposure at each work place (7) .…”
Section: Discussionmentioning
confidence: 99%